Sursundari figures on the Pillars of the Mukhamandapa - Temples of India Project Team (Jio Institute, 2024)
The pillars of the mukhamandapa (front porch) show youthful and charming sursundaris (celestial damsels) with captivating beauty. While many of these figures are badly damaged or lost, the intact figures show the voluptuous bodies of these sursundaris, covered with translucent, fine pieces of cloth, standing on lotus flowers. Their appearance is further enhanced by the jewelleries and elaborate hairstyles.